Dihedral corner reflector antenna excited by a probe inside rectangular ring - Lamultree, S.; Phongcharoenpanich, C.; Kosulvit, S.; Krairiksh, M. (My University, 2003)
This paper proposes a dihedral corner reflector excited by a probe inside rectangular ring. The antenna structure is simple. The radiation characteristics of the antenna for various spacing between a probe inside rectangular ring and the dihedral corner reflector are analyzed. The numerical results of the radiation pattern, elevational and azimuthal beam peak in E-plane and H-plane, beamwidth and maximum directivity are substantially investigated. In addition, these characteristics are also compared among the included angles of 30°, 45°, 60° and 90° of dihedral corner reflector. The result of the analysis is very useful to design the antenna of high directivity with unidirectional beam.
Keywords: Antenna radiation patterns; Costs; Dielectric losses; Directional antennas; Feeds; Horn antennas; Information technology; Microstrip antennas; Probes; Reflector antennas